Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Higher Order Thinking Skills (HOTS) Materi Bangun Ruang Kelas V SD Negeri 54 Banda Aceh - Israin, Nadhyla Laily; Fauzi, Fauzi; Yamin, M. (Universitas Syiah Kuala, 2022)
This review plans to perceive how the cycle and consequences of creating Understudy Worksheets (LKPD) in light of Higher Request Thinking Abilities (HOTS) materials for study hall development at SD 54 Negeri Banda Aceh. The examination technique utilized is Innovative work (Research and development) with the Plomp advancement model which incorporates: Beginning Examination Stage, Plan Stage, Acknowledgment Stage, Test Stage, Assessment and Correction and Execution Stage. The subjects in this review were all 5th grade understudies at SDN 54 Banda Aceh, adding up to 25 individuals, 13 young men and 12 young ladies. Which comprises of 5 individuals for limited scope and 20 individuals for enormous scope. The instruments utilized are approval sheets by validators, understudy reaction sheets, understudy worksheets in view of HOTS and assessment test sheets. The information examination procedure in this study utilized quantitative examination, which comprised of LKPD approval investigation, LKPD down to earth examination, and LKPD adequacy investigation. what's more, research results. That's what the outcomes showed: 1) the HOTS-based LKPD created had met the substantial models. This should be visible from the aftereffects of the material master approval acquired a normal level of 94.09% with generally excellent measures. The aftereffects of media master approval acquired a normal level of 93.85% with awesome models, 2) the HOTS-based LKPD created had met the viable standards seen from understudy reactions and LKPD item preliminaries. This should be visible from the reasonableness test information that was tried on two scales, limited scope and enormous scope. the limited scale test got a normal of 84.40% remembered for the generally excellent classification, and the huge scope test got the awesome class with a normal of 83.2%, 5) HOTS-based worksheets created have met the successful measures. This should be visible from the gaining results of understudies seen from the assessment test. Understudies who have scores over the KKM are 22 understudies with a level of 88%. In the interim, there are 3 understudies who have scores beneath the KKM with a level of 12%